STRATEGY FOR IMPROVING ECOTOURISM BRANDING THROUGH MANGROVE BATIK IN BLIMBING MALANG - Santoso, Rudi; Riyanto, Darwin Yuwono; Fianto, Achamad Yanu Alif (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
This community service activity aims to help ecotourism business actors to increase visits through destination branding strategies. The problem faced by ecotourism business players is that business income has barely developed, especially after the pandemic. One of the Micro, Small and Medium Enterprise sectors affected is hand-written batik. This assistance and training was provided to the Malang Mangrove Batik MSME Group, which consists of 40 members of Batik entrepreneurs throughout Malang City Regency. The lack of visitors and purchasing power which is still only starting to increase after the pandemic also has an impact on the income of MSMEs. Apart from that, several problems with mangrove tourism are caused by not optimal social media branding, lack of cooperation from local communities for branding, lack of information on tourist destinations in mass media, lack of massive campaigns on social media, lack of understanding of the potential and uniqueness of mangrove tourism, etc. have a mangrove tourism promotion strategy plan. This activity seeks to restore income for MSMEs through a destination branding strategy for mangrove batik ecotourism. One of the efforts made is branding mangrove batik. This activity includes 5 stages starting from market analysis, brand identity, brand launch and introduction, brand implementation, and monitoring/evaluation. The results of branding activities show a significant increase in awareness of mangrove batik both in terms of brand, engagement and market segmentation.